Trust in Mono-Ethnic and Mixed-Ethnic Associations in Penang - James K. Campbell ,; Yen Siew Hwa , (Kajian Malaysia, 2007)
Investigation into trust has become a topical issue in current social science research. This is, in large part, a result of a perception that trust in institutions has declined markedly in the past two decades. This paper investigates trust in some of Penang’s civil associations as a way of measuring the health of social capital in Penang. It focuses on issues of trust and diversity since both are critical issues in Malaysian society in general and civil associations in particular. We began our analysis expecting higher forms of trust among members in the mono-ethnic associations, based on the power of bonding. However, findings from this study tend to suggest that rather than leading to lesser trust and infectiveness, involvement in mixed-ethnic associations have in fact generated higher trust among their members. These findings reveal an interesting corrective to more pessimistic view on the relationship between trust and diversity. Data from this study also provide important insight into how bridging between different people in associations marked by diversity can accentuate trust over and above the levels found in associations were bonding between like types is the dominant characteristic. The data also indicate that for both, mono-ethnic and mixed-ethnic associations, it is the extent of members’ involvements in their associations that form trust and not vice versa.